2016
DOI: 10.5665/sleep.5444
|View full text |Cite
|
Sign up to set email alerts
|

Orexin Receptor Antagonism Improves Sleep and Reduces Seizures inKcna1-null Mice

Abstract: Dual orexin receptor antagonists may be an effective sleeping aid in epilepsy, and warrants further study on their somnogenic and ant-seizure effects in other epilepsy models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 55 publications
10
75
0
Order By: Relevance
“…The Kv1.1KO mouse is a model of temporal lobe epilepsy that exhibits severe and frequent spontaneous recurrent seizures (SRS) (Simeone et al, 2013, 2014a,b; Fenoglio-Simeone et al, 2009a,b Kim et al, 2015; Roundtree et al, 2016). We have previously demonstrated that the KD is highly efficacious in Kv1.1KO mice attenuating seizures by 70–80% (Fenoglio-Simeone et al, 2009a; Kim et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Kv1.1KO mouse is a model of temporal lobe epilepsy that exhibits severe and frequent spontaneous recurrent seizures (SRS) (Simeone et al, 2013, 2014a,b; Fenoglio-Simeone et al, 2009a,b Kim et al, 2015; Roundtree et al, 2016). We have previously demonstrated that the KD is highly efficacious in Kv1.1KO mice attenuating seizures by 70–80% (Fenoglio-Simeone et al, 2009a; Kim et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Seizure frequency was quantified and further weighted for Racine scale severity to calculate a seizure burden index score for each mouse. A seizure burden index score provides an important consolidated metric to convey the effect of a given treatment on both the frequency and severity of seizures (Simeone et al 2014a; Barker-Haliski et al, 2015; Roundtree et al, 2016). Similar to our previous findings (Fenoglio-Simeone et al, 2009a,b Kim et al, 2015), KD treatment decreased seizure frequency and burden of Kv1.1KO mice by ~70% (Fig.4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a buildup of CO 2 in the lungs will elevate blood CO 2 levels to signal peripheral and central chemoreceptors to increase respiration rate, which in turn stabilizes blood gasses. 38 Therefore, increased orexin neuronal activation may be a central driver of increased respiratory responses of Kcna1 À/À mice. Respiratory drive reflects the volume of air that enters and exits the lungs in one cycle normalized to inspiration time.…”
Section: Mch Paradoxically Provokesmentioning
confidence: 99%